A reading in the educational opinions of Ibn Khaldun from sociology of education’ perspective - Yaiche, Ouassila; Benmissi, Zoubeida Mounya (Al-Adab Journal, 2021)
This paper aims to highlight Ibn Khaldun’s leading opinions in the field of education and his didactic and pedagogical contributions that have gone beyond his era to meet the demands of contemporary sociology of education. These views full of Islamic spirit were expressed in his famous Muqaddima The historian and sociologist Ibn Khaldun discussed the importance of education in forming a good human being through analyzing the essence of education, the factors of its prosperity, the types of sciences and the ways to achieve them. Ibn Khaldun mentioned the different sciences in his time, along with details about their topics, methods, how to use them and take benefit from them. And he also rejected some sciences because of their ability to spread corruption, harm people and weaken their beliefs. Moreover, this article presents the qualifications and ethics of the teacher, who is the pillar of the educational process and the main determinant of its outcomes, it also highlights a set of qualities that the learner should be equipped with in his scientific career to achieve his goals and objectives; as well as discussing the teaching strategies that Ibn Khaldun criticized, assessed, then suggested a new one.